Types Of Reading Comprehension Questions Of English National Examination For Senior High School Students - Hidayati, Sulistyani, Prof. Dr. Endang Fauziati, M. Hum, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
This research has the objectives to: 1) unearth the types of reading comprehension questions of English national examination in year 2011-2015; 2) reveal the frequecy of each type of questions of English national examination in year 2011-2015; and 3) illustrate the differences and similarities of types of English national examination for senior high school students in year 2011-2015. The type of the research is qualitative research. This research uses content analysis because it takes the content of the items in English final examination. The main data source is the document of English National Examination for senior high school from 2011 to 2015.The data of the research is the test items of English National Examination for senior high school from 2011 to 2015. The technique of collecting thedata used documentary technique. The analysis is focused on the English reading comprehension questions that were written in multiple choice form. This research applies constant comparative method which compares the datas or the categories with the other one constantly. The conclusion of the research is that the types of reading comprehension questions of English national examination for senior high school students of year 2011-2015 reveals that there are 6 types of reading comprehensions questions used in English national examination of 2011 to 2015, they are: vocab in context, inferential comprehension, function, literal comprehension, specific and evaluation. Based on the theory of reading comprehensions questions of GMAT and Barret's taxonomy, the types of reading comprehensions questions used in English national examination of 2011 to 2015 are less of variations of question types. There is a significant difference of frequency of each type of reading comprehension questions of each year. The most frequently tested of the question type from 2011 to 2015 is the inferential type of questions. In the second place is literal comprehension. The vocab in context has the third position of number of cases. The function, the specific and the evaluation types are fewer tested in the items test. There are differences and similarities among the types of reading question types of 2011 to 2015. The differences are lied on: 1) The frequency of the number of cases; 2) The number of cases distribution of question types are not balanced of each year. The similarities among of them are: 1) Aspects of the question types; 2) The dominant of question types tested of each year. The balancing of the frequency and number of cases distribution is better in arranging the question items test. Keywords: reading comprehension, reading questions types, national examination.